Metal–dielectric hybrid nanoantennas for efficient frequency conversion at the anapole mode - Gili, Valerio F.; Ghirardini, Lavinia; Rocco, Davide; Marino, Giuseppe; Favero, Ivan; Roland, Iännis; Pellegrini, Giovanni; Duò, Lamberto; Finazzi, Marco; Carletti, Luca; Locatelli, Andrea; Lemaître, Aristide; et al. (Beilstein Journal of Nanotechnology, 2018)
Background: Dielectric nanoantennas have recently emerged as an alternative solution to plasmonics for nonlinear light manipulation at the nanoscale, thanks to the magnetic and electric resonances, the strong nonlinearities, and the low ohmic losses characterizing high refractive-index materials in the visible/near-infrared (NIR) region of the spectrum. In this frame, AlGaAs nanoantennas demonstrated to be extremely efficient sources of second harmonic radiation. In particular, the nonlinear polarization of an optical system pumped at the anapole mode can be potentially boosted, due to both the strong dip in the scattering spectrum and the near-field enhancement, which are characteristic of this mode. Plasmonic nanostructures, on the other hand, remain the most promising solution to achieve strong local field confinement, especially in the NIR, where metals such as gold display relatively low losses.Results: We present a nonlinear hybrid antenna based on an AlGaAs nanopillar surrounded by a gold ring, which merges in a single platform the strong field confinement typically produced by plasmonic antennas with the high nonlinearity and low loss characteristics of dielectric nanoantennas. This platform allows enhancing the coupling of light to the nanopillar at coincidence with the anapole mode, hence boosting both second- and third-harmonic generation conversion efficiencies. More than one order of magnitude enhancement factors are measured for both processes with respect to the isolated structure.Conclusion: The present results reveal the possibility to achieve tuneable metamixers and higher resolution in nonlinear sensing and spectroscopy, by means of improved both pump coupling and emission efficiency due to the excitation of the anapole mode enhanced by the plasmonic nanoantenna.
Keywords: nanophotonics; nonlinear optics; plasmonics; second-harmonic generation; semiconductors

(untitled) - Franken, P. A.; Hill, A. E.; Peters, C. W.; Weinreich, G. (Phys. Rev. Lett., 1961)

(untitled) - Cerullo, G.; De Silvestri, S. (Rev. Sci. Instrum., 2003)

(untitled) - Sipe, J. E.; Moss, D. J.; van Driel, H. M. (Phys. Rev. B, 1987)

(untitled) - Petrocelli, G.; Pichini, E.; Scudieri, F.; Martellucci, S. (J. Opt. Soc. Am. B, 1993)

(untitled) - Bottomley, D. J.; Lüpke, G.; Mihaychuk, J. G.; van Driel, H. M. (J. Appl. Phys., 1993)

(untitled) - Chen, X.; Nadiarynkh, O.; Plotnikov, S.; Campagnola, P. J. (Nat. Protoc., 2012)

(untitled) - Steel, W. H.; Walker, R. A. (Nature, 2003)

(untitled) - Liu, S.; Vabishchevich, P. P.; Vaskin, A.; Reno, J. L.; Keeler, G. A.; Sinclair, M. B.; Staude, I.; Brener, I. (Nat. Commun., 2018)

(untitled) - Krasnok, A.; Tymchenko, M.; Alù, A. (Mater. Today, 2018)

(untitled) - Caldarola, M.; Albella, P.; Cortés, E.; Rahmani, M.; Roschuk, T.; Grinblat, G.; Oulton, R. F.; Bragas, A. V.; Maier, S. A. (Nat. Commun., 2015)

(untitled) - Kauranen, M.; Zayats, A. V. (Nat. Photonics, 2012)

(untitled) - Celebrano, M.; Wu, X. F.; Baselli, M.; Grossmann, S.; Biagioni, P.; Locatelli, A.; De Angelis, C.; Cerullo, G.; Osellame, R.; Hecht, B.; Duò, L.; Ciccacci, F.; et al. (Nat. Nanotechnol., 2015)

(untitled) - Baselli, M.; Baudrion, A.-L.; Ghirardini, L.; Pellegrini, G.; Sakat, E.; Carletti, L.; Locatelli, A.; De Angelis, C.; Biagioni, P.; Duò, L.; Finazzi, M.; Adam, P.-M.; et al. (Plasmonics, 2017)

(untitled) - Marino, G.; Segovia, P.; Krasavin, A. V.; Ginzburg, P.; Olivier, N.; Wurtz, G. A.; Zayats, A. V. (Laser Photonics Rev., 2018)

(untitled) - Kuznetsov, A. I.; Miroshnichenko, A. E.; Brongersma, M. L.; Kivshar, Y. S.; Luk'yanchuk, B. (Science, 2016)

(untitled) - Smirnova, D.; Kivshar, Y. S. (Optica, 2016)

(untitled) - Shcherbakov, M. R.; Neshev, D. N.; Hopkins, B.; Shorokhov, A. S.; Staude, I.; Melik-Gaykazyan, E. V.; Decker, M.; Ezhov, A. A.; Miroshnichenko, A. E.; Brener, I.; Fedyanin, A. A.; Kivshar, Y. S. (Nano Lett., 2014)

(untitled) - Shcherbakov, M. R.; Shorokhov, A. S.; Neshev, D. N.; Hopkins, B.; Staude, I.; Melik-Gaykazyan, E. V.; Ezhov, A. A.; Miroshnichenko, A. E.; Brener, I.; Fedyanin, A. A.; Kivshar, Y. S. (ACS Photonics, 2015)

(untitled) - Grinblat, G.; Li, Y.; Nielsen, M. P.; Oulton, R. F.; Maier, S. A. (ACS Nano, 2017)

(untitled) - Miroshnichenko, A. E.; Evlyukhin, A. B.; Yu, Y. F.; Bakker, R. M.; Chipouline, A.; Kuznetsov, A. I.; Luk’yanchuk, B.; Chichkov, B. N.; Kivshar, Y. S. (Nat. Commun., 2015)

(untitled) - Wang, R.; Dal Negro, L. (Opt. Express, 2016)

(untitled) - Gongora, J. S. T.; Miroshnichenko, A. E.; Kivshar, Y. S.; Fratalocchi, A. (Nat. Commun., 2017)

(untitled) - Baranov, D. G.; Verre, R.; Karpinski, P.; Käll, M. (ACS Photonics, 2018)

(untitled) - Pu, M.; Ottaviano, L.; Semenova, E.; Yvind, K. (Optica, 2016)

(untitled) - Morais, N.; Roland, I.; Ravaro, M.; Hease, W.; Lemaître, A.; Gomez, C.; Wabnitz, S.; De Rosa, M.; Favero, I.; Leo, G. (Opt. Lett., 2017)

(untitled) - Savanier, M.; Ozanam, C.; Lanco, L.; Lafosse, X.; Andronico, A.; Favero, I.; Ducci, S.; Leo, G. (Appl. Phys. Lett., 2013)

(untitled) - Carletti, L.; Locatelli, A.; Stepanenko, O.; Leo, G.; De Angelis, C. (Opt. Express, 2015)

(untitled) - Gili, V. F.; Carletti, L.; Locatelli, A.; Rocco, D.; Finazzi, M.; Ghirardini, L.; Favero, I.; Gomez, C.; Lemaître, A.; Celebrano, M.; De Angelis, C.; Leo, G. (Opt. Express, 2016)

(untitled) - Camacho-Morales, R.; Rahmani, M.; Kruk, S.; Wang, L.; Xu, L.; Smirnova, D. A.; Solntsev, A. S.; Miroshnichenko, A. A.; Tan, H. H.; Karouta, F.; Naureen, S.; Vora, K.; et al. (Nano Lett., 2016)

(untitled) - Liu, S.; Vabishchevich, P. P.; Vaskin, A.; Reno, J. L.; Keeler, G. A.; Sinclair, M. B.; Staude, I.; Brener, I. (arXiv, 2017)

(untitled) - Timpu, F.; Sergeyev, A.; Hendricks, N. R.; Grange, R. (ACS Photonics, 2017)

(untitled) - Timpu, F.; Hendricks, N. R.; Petrov, M.; Ni, S.; Renaut, C.; Wolf, H.; Isa, L.; Kivshar, Y.; Grange, R. (Nano Lett., 2017)

(untitled) - Rocco, D.; Gili, V. F.; Ghirardini, L.; Carletti, L.; Favero, I.; Locatelli, A.; Marino, G.; Neshev, D. N.; Celebrano, M.; Finazzi, M.; Leo, G.; De Angelis, C. (Photonics Res., 2018)

(untitled) - Guo, R.; Rusak, E.; Staude, I.; Dominguez, J.; Decker, M.; Rockstuhl, C.; Brener, I.; Neshev, D. N.; Kivshar, Y. S. (ACS Photonics, 2016)

(untitled) - Decker, M.; Pertsch, T.; Staude, I. (Philos. Trans. R. Soc., A, 2017)

(untitled) - Kruk, S.; Weismann, M.; Bykov, A. Y.; Mamonov, E. A.; Kolmychek, I. A.; Murzina, T.; Panoiu, N. C.; Neshev, D. N.; Kivshar, Y. S. (ACS Photonics, 2015)

(untitled) - Shibanuma, T.; Grinblat, G.; Albella, P.; Maier, S. A. (Nano Lett., 2017)

(untitled) - Ghirardini, L.; Carletti, L.; Gili, V.; Pellegrini, G.; Duò, L.; Finazzi, M.; Rocco, D.; Locatelli, A.; De Angelis, C.; Favero, I.; Ravaro, M.; Leo, G.; et al. (Opt. Lett., 2017)

(untitled) - Carletti, L.; Rocco, D.; Locatelli, A.; De Angelis, C.; Gili, V. F.; Ravaro, M.; Favero, I.; Leo, G.; Finazzi, M.; Ghirardini, L.; Celebrano, M.; Marino, G.; et al. (Nanotechnology, 2017)

(untitled) - Gehrsitz, S.; Reinhart, F. K.; Gourgon, C.; Herres, N.; Vonlanthen, A.; Sigg, H. (J. Appl. Phys., 2000)

(untitled) - Radescu, E. E.; Vaman, G. (Phys. Rev. E, 2002)